FIRE PERFORMANCE OF NON-LOADBEARING LIGHT STEEL FRAMING WALLS – NUMERICAL AND SIMPLE CALCULATION METHODS - Piloto, Paulo; Khetata, Mohamed; Gavilán, Ana (MATTER: International Journal of Science and Technology, 2017)
Light steel frame and prefabricated panels are widely used in non-loadbearing walls, with direct application to steel framed buildings. Such panels consist of steel sections (studs and tracks) with gypsum plasterboard layers attached to the flanges on the outside and use insulation material in the cavities. The fire resistance is usually provided by one or more layers of panels and by the insulation material. This investigation evaluates the thermal behaviour of the unexposed surface and of the nodal internal layers, using numerical simulations and a simple calculation method, assuming that heat flow is almost one-dimensional. The fire resistance is compared for both models using a cross section of the wall with one and two gypsum layers. The insulation criterion is the only one used for the calculation of the fire resistance, based on the calculation of the average and maximum temperature of the unexposed surface above the initial average temperature. Good approach was achieved by the simple calculation model, when optimum effective width is assumed for the model.